A life-time reproducible mechano-luminescent paint for the visualization of crack propagation mechanisms in concrete structures. (August 2017) - Timilsina, Suman; Bashnet, Ramesh; Kim, Seong Hoon; Lee, Kwang Ho; Kim, Ji Sik
Highlights: In-situ crack initiation and propagation were visualized with an aid of ML paint. Fatigue strength of ML paint is good enough to be applied on normal strength concrete. ML paint showed excellent optical durability. The mechanism of photon emission is identical throughout the life of ML paint. Abstract: Mechano-luminescent (ML) paint consisting of SrAl2 O4 :Eu 2+, Dy 3+ powders and transparent epoxy resin could reveal the complex crack initiation and propagation evolved from the Brazilian test of conventional concrete. ML paint also showed excellent fatigue resistance in terms of mechanical strength and optical ML durability, even in weatherproof. Although the intensity of emitted photons from ML paint has been reduced as the number of repetitive stress cycles increased, however, the deterioration of ML intensity with the variation of additive stress cycle was less than 5% in the cases of high cycle failure. Consequently, the life time reproducibility of ML paint allows the possibility to characterize the long-term integrity of various concrete structures.